X‐Ray Diffractive Imaging: Needle‐Like Ferroelastic Domains in Individual Ferroelectric Nanoparticles (Adv. Electron. Mater. 5/2020). (11th May 2020) - Liu, Zhen; Schold, Elijah; Karpov, Dmitry; Harder, Ross; Lookman, Turab; Fohtung, Edwin
Abstract : In article 1901300, Edwin Fohtung and co‐workers demonstrate an X‐ray Bragg coherent diffractive imaging technique to spatially resolve the evolution of nanoscopic ferroelastic needle‐like domains in individual BaTiO3 nanocrystals under external pressure. This provides a new paradigm for domain‐boundary engineering and potential for nanoscale functional devices aided by pressure‐induce structural phase transitions and ferroelectric phase transformation.